Implementing Youtube-Based Video As An Teaching Media To Teach Speaking Through Zoom Application - Rubai'ah; Ammang Latifa; Ika Yanti Ziska (La Parole : Journal of Language Teaching and Pedagogy, 2020)
This research-based on the students’ problem regarding English teaching especially speaking. It was caused by the teaching media applied in the classroom, where the students not interested to study. This problem was also caused by several factors such as the students in the classroom were bored and not motivated in teaching taught by using media. Consequently, the students’ speaking ability was low. Therefore, the objectives of the research are To find out whether or not the use of YouTube-based video via Zoom able to make students interesting to start speaking at eighth-grade students of UPTD SMP Negeri 7 Parepare. And how it can give progress to students speaking ability. The researcher applied a pre-experimental design (quantitative descriptive one tail), with two groups of pretest and posttest design. The researcher carries out the material by using YouTube-based video Via Zoom. The population of this research was the eighth-grade students at UPTD SMP Negeri 7 Parepare academic year 2020/2021. The sample of the research was taken by using cluster random sampling which consisted of 22 students from one class taken from the population of the eighth-grade student of UPTD SMP Negeri 7 Parepare, VIII.1. The result of the data analysis showed that the students speaking ability were improved, showed by the mean score of the pretest was (53,77). Besides that the mean score of the posttest was (72,54). It showed that the speaking ability of the eighth-grade students at UPTD SMP Negeri 7 Parepare was got progress by implementing YouTube-based video.